جہاد اور مستشرقین :"سیرۃ النبی" اور "ضیاء النبی" کی روشنی میں ایک مطالعہJihād and Orientalists: A Study in the Light of “Sīrat al-Nabī” and “Zīāʻ al-Nabī" (Al-Qamar, 2024)
In the 19th century, the intellectual interaction between Muslims and Orientalists led to both positive and negative outcomes. The first notable Muslim scholar to address Orientalist critiques was Sir Syed Ahmed Khan, who responded to Sir William Muir's objections in his works on the life of Prophet Muhammad (peace be upon him). Later, Shibli Nomani's Seerat-un-Nabi addressed the concerns raised by Margoliouth, and this scholarly engagement continued. Muslim scholars, recognizing their academic, religious, and missionary responsibilities, attempted to counter Orientalist misconceptions about jihad. Among them, Pir Karam Shah al-Azhari made significant contributions.This study examines the Orientalist perspective on jihad and their objections, analyzing them in the context of Seerat-un-Nabi and Zia-un-Nabi. Key areas of discussion include coercion, jizya, and the nature of jihad—whether it was proactive or defensive. An analytical comparison of these aspects highlights areas of agreement and contention.By the conclusion of this article, it becomes evident why primary sources are crucial in critiquing Orientalist narratives. Additionally, it outlines the key areas where further academic work is required to refute misconceptions regarding jihad and how Muslim scholars can effectively fulfill their intellectual, religious, and missionary duties.
Keywords: Seerat; Orientalism; Jihad; Methodology